Potassium‐sulfur batteries: Status and perspectives - Xinyu Zhao; Yan Lu; Zhengfang Qian; Renheng Wang; Zaiping Guo (EcoMat, 2020)
Abstract This review article aims to provide insight into the research status of the potassium‐sulfur (K‐S) system, feature the challenges facing this technology, and present possible research directions for the realization of its practical applications. We begin with an introduction to the fundamental electrochemistry of K‐S batteries and emphasize the distinctions between K‐S technology and the well‐established lithium‐sulfur (Li‐S) system. Then, we focus on the development of the materials involved in K‐S batteries in terms of cathodes, K anodes, and various electrolyte systems. Finally, we provide several possible research directions to make the K‐S system a reality, with the emphasis, from our point of view, on the attempts to construct practical parameters for K‐S batteries by adopting the critical metrics of the current Li‐S system.